Determinants of banking fee income in the EU banking industry: Does market concentration matter? - Karolína Růžičková; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2015)
The wide change of banking models over last few decades has led to an increasing share of fee and commission income of banks. In this paper we deal with determinants of banking fees in the European Union with special emphasis on market concentration based on EU-27 data from 2007 to 2012. For the estimation we use System Generalized Method of Moments, which is appropriate for dynamic panel data, allows for time invariant and lagged dependent variables and is able to deal with endogeneity. We conclude that banks facing higher competition tend to expand more aggressively into non-traditional activities and therefore they report higher fee income shares. Moreover, we found that a higher equity to assets ratio is related with higher shares of fee income since by expanding into non-traditional businesses the bank needs more capital to prevent the potential risks of the new activity. Surprisingly, a high deposits to assets ratio tends to increase the fee income share, which may be possibly attributed to relatively high switching costs and to close relationship between depositor and bank in the EU banking sector. However, macroeconomic conditions do not seem to have a significant impact on the net fee and commission income share.
Keywords: C23; G21; L25; 330; bank; fee and commission income; market concentration; GMM system